2007
DOI: 10.1517/14740338.6.3.267
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of antiepileptic drugs on bone mineral density in children

Abstract: Bone mineral content (BMC) or density (BMD) may be decreased in children with epilepsy either as a consequence of the epilepsy, the condition that caused the epilepsy or the treatment for epilepsy. This paper investigates the effects of antiepileptic drugs (AEDs) on BMD in children. A systematic search of Pubmed resulted in 14 papers that described changes in BMD in children on AEDs. For phenytoin, one study failed to show a decrease in femur BMD, whereas another study reported a decrease in total body and spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 48 publications
(91 reference statements)
1
18
0
1
Order By: Relevance
“…Observational studies have suggested that chronic treatment with AEDs altered the bone metabolism and might be a risk factor for suboptimal bone mineral density and osteopenia in children [23,55]. It has been hypothesised that there are direct and indirect mechanisms that could link AEDs with these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies have suggested that chronic treatment with AEDs altered the bone metabolism and might be a risk factor for suboptimal bone mineral density and osteopenia in children [23,55]. It has been hypothesised that there are direct and indirect mechanisms that could link AEDs with these effects.…”
Section: Discussionmentioning
confidence: 99%
“…This offers a pathophysiological explanation for why children treated with AEDs may have low BMD compared with healthy children. However, results from epidemiological studies supporting this biochemical hypothesis are still inconsistent [23,55]. Moreover, some studies reported abnormalities in the bone metabolism of patients treated with AEDs independently of vitamin D deficiency [3,67,68].…”
mentioning
confidence: 99%
“…Final body height and body weight may thus be impaired when T1D debuts in childhood. Smaller bones may appear 'thinner' by DXA than larger bones because of the 2D scan technique applied by DXA (65), so patients with impaired growth may be deemed to have decreased BMD if they are not compared to subjects with similar body configurations. Patients with T2D, on the other hand, are often obese and thus have larger body frames than those of patients with T1D.…”
Section: Differences Between T1d and T2dmentioning
confidence: 99%
“…More recently, studies in children with intractable epilepsy have consistently shown that a prolonged KD can induce a progressive loss of bone mineral content (BMC) associated with poor bone health status, probably as a consequence of a chronic acidic environment [15,16]. However, the long-term effects of a KD on bone mineral status of GLUT-1 DS patients are currently unknown.…”
Section: Introductionmentioning
confidence: 99%